A SCIENTIFIC REVIEW OF MOOLAM (ANO RECTAL DISEASES)-YUGIS VERSION (International Journal of Ayurveda and Pharma Research, 2018)
Worldwide, the overall prevalence of an ano rectal disease in the general population is estimated to be 4.4%. The faulty dietary pattern and life style , hereditary factors are important etiological factors of this disease. As per saint Yugi  Moolam is classified as 21 types based on clinical symptoms and size, shape, colour of the pile mass which includes some of the ano-rectal diseases. The diet and deeds which influences the vital humors Vatham  (Intestinal peristaltic movement ) and Pitham (metabolism and absorption) of food stuffs are said to be major causative factors of this disease. As per Yugis version the following ano rectal diseases under Moola noi have been categorized as, Neer moolam (Inflammatory bowel disease), Aazhi moolam (strangulated haemorrhoids), Sittru moolam (adenomatous colorectal polyps), Varal moolam (colorectal non- neoplastic polyps), Seezh moolam (kaposis sarcoma), Silaethuma moolam (anal warts condyloma), Thondha moolam (rectal cancer), Vinai moolam (irritable bowel syndrome), Powthira moolam (anal fistula), Kutha moolam (rectal prolapse), Ratha moolam (internal haemorrhoids 1st degree -bleeding piles), Mega moolam (gonococcal proctitis), Vaatha moolam (interno-external hemorrhoids), Pitha moolam (prolapsed haemorrhoids), Surukku moolam (anal stenosis), Mulai moolam (sentinel pile), Savvu moolam (perianal tuberclosis). This paper focuses the scientific basis of etiology and classification of Moolam by saint Yugi.